PENGARUH RETURN ON ASSET DAN NET PROFIT MARGIN TERHADAP PRAKTIK PERATAAN LABA PADA PERUSAHAAN AUTOMOTIF YANG TERCATAT DI BURSA EFEK INDONESIA - Sundari, Siti; Sari, Rida Perwita (Journal of Accounting and Strategic Finance, 2011)
The stock market is an institution which has a characteristic intermeditasi and competitive advantage and a greater level of openness compared to other institutions. One of the parameters used to measure the performance of management is profit, the tendency of investors focused on earnings information regardless of the procedures used to generate information on earnings, thus encouraging the emergence of Disfunctional Behavior (improper conduct). The form of improper conduct arising in relation to earnings is the practice of income smoothing (income smoothing). This study uses secondary data obtained from financial statement data automotive sector companies listed in Indonesia Stock Exchange in 2003 to 2007. Purposive sampling technique of sampling, with independent variables Return On Assets, Net Profit Margin, and the dependent variable is earnings smoothing. Statistical analysis used to test the effect of return on assets and net profit margin on the practice of income smoothing is a logistic regression analysis. The results of this study concluded that the net profit margin effect on income smoothing, while return on assets does not affect the income smoothing.   Keywords: Net Profit Margin, Return On Assets, Income smoothing